#### Answer

$-\frac{1}{625},-\frac{1}{25},1$

#### Work Step by Step

$-5^{-2-2}=-5^{-4}=-\frac{1}{625}$
$-5^{0-2}=-5^{-2}=-\frac{1}{25}$
$-5^{2-2}=-5^0=1$

Published by
Prentice Hall

ISBN 10:
0133186024

ISBN 13:
978-0-13318-602-4

$-\frac{1}{625},-\frac{1}{25},1$

$-5^{-2-2}=-5^{-4}=-\frac{1}{625}$
$-5^{0-2}=-5^{-2}=-\frac{1}{25}$
$-5^{2-2}=-5^0=1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.